Antitumor activity of alantolactone in lung cancer cell lines NCI‐H1299 and Anip973. Issue 9 (5th July 2019) - Liu, Jianli; Yang, Zhijun; Kong, Yuchi; He, Yin; Xu, Yongliang; Cao, Xiangyu
Abstract: Alantolactone is a sesquiterpene lactone extracted from Inula helenium L . plants possessing many biological activities, including anti‐inflammatory, antiproliferation, and antimicrobial. The inhibitory effects and the underlying mechanisms of alantolactone on lung cancer cells NCI‐H1299 and Anip973 were investigated in this study. The results showed that alantolactone could decrease cell viability and induce cell apoptosis of NCI‐H1299 and Anip973. After the cells were treated with alantolactone, the expression of Bcl‐2 decreased, while the expression of Bax increased, the expression of MMP‐9, MMP‐7, and MMP‐2 gradually decreased after alantolactone treatment. Furthermore, results showed that alantolactone could activate p38 MAPK pathway and suppress NF‐κB pathway, which are involving in lung cancer development. These results indicated that alantolactone was a potential agent for lung cancer treatment. Practical applications: Lung cancer is one of the most common contributors of cancer death in the world. Chemoprevention and chemotherapy with natural substances are prospective methods for lung cancer treatment. In recent years, the anti‐cancer activity of various sesquiterpene lactones has attracted a great deal of interest. Alantolactone is the major active sesquiterpene lactones isolated from Inula helenium L, which is used as a medicine in ancient Romans due to wide range of pharmacological activities. The results obtained from this study revealed the inhibitory effects of alantolactone on lung cancer cells and might provide some experimental basis for prevention and treatment of lung cancer with alantolactone. Abstract : Alantolactone induced apoptosis and suppressed migration of lung cancer cell lines NCI‐H1299 and Anip973 via regulating p38MAPK and NF‐κB pathways.